Extracellular matrix coating improves the biocompatibility of polymeric heart valves. Issue 46 (4th November 2020) - Wu, Binggang; Jin, Linhe; Ding, Kailei; Zhou, Yonghua; Yang, Li; Lei, Yang; Guo, Yingqiang; Wang, Yunbing
Abstract : Prosthetic heart valve replacement is an effective therapy for patients with valvular heart disease. Abstract : Prosthetic heart valve replacement is an effective therapy for patients with valvular heart disease. New-type polymer materials provide potential choices of material for preparing prosthetic heart valves. In this study, we focused on enhancing the biocompatibility of polystyrene- block -isobutylene- block -styrene (SIBS) by surface modification with an extracellular matrix (ECM). Experimental results demonstrated that the ECM coating increased the adsorption resistance against protein and platelets. SIBS coated with an ECM adsorbed much less bovine serum albumin and fibrinogen (5.38 μg cm −2 and 31.53 μg cm −2, respectively) than the original material (90.84 μg cm −2 and 132.38 μg cm −2, respectively). The relative platelet adsorption of the ECM-modified SIBS was lower than that of SIBS (0.04 versus 0.10). Moreover, the surface coating could also reduce endothelial cytotoxicity, suppress the immune response, and potentially induce tissue regeneration. In conclusion, ECM coating improved the biocompatibility of SIBS effectively.